An Analysis of Student Anxiety Affecting on Online Learning on Conceptual Applications in Physics: Synchronous vs. Asynchronous Learning - Parinda Phanphech; Tanes Tanitteerapan; Narong Mungkung; Somchai Arunrungrusmi; Charathip Chunkul; Apidat Songruk; Toshifumi Yuji; Hiroyuki Kinoshita (MDPI AG, 2022)
This study examines the impact of students' anxiety, due to online learning, in different learning environments: a synchronous (Zoom) and asynchronous learning environment (YouTube) to compare students' conceptual understanding of electric circuits. Multiple linear regression and factor analyses were conducted to examine the factor of students' anxiety and conceptual understanding. A sample of 99 vocational students participated in the study, including YouTube (n = 49) and Zoom (n = 50) groups. The DIRECT was used to diagnose test for conceptual understanding in the electric circuits, and OTAI was used to assess anxiety in online learning test. The OTAI consists of three factors: psychological, physiological, and online. The results showed that students' anxiety, in some factors, affected their conceptual understanding of the electric circuits in both groups. However, there was a significant increase in conceptual understanding in both treatment groups. Although the students' conceptual understanding had a slight increase, online learning has to improve to reduce the anxiety of learners.